Efficient Oracle Attacks on Yeung-Mintzer and Variant Authentication Schemes - Wu, Jinhai; Zhu, Bin Benjamin; Li, Shipeng; Lin, Fuzong (Institute of Electrical and Electronics Engineers, Inc., 2004)
The Yeung-Mintzer (Y-M) image authentication scheme has been well studied. Several vulnerabilities and modified schemes to fix them have been reported. In this paper, we propose a novel oracle attack on the Y-M scheme and its variations. Our attack is very different from the previously proposed attacks. A single authenticated image plus access to a verifier (oracle) is enough in our attack. The verifier returns if a testing image is authentic or not. Locations of tampered pixels are not needed. To launch the attack, a single pixel is modified and the resulting image is sent to the verifier. Observation of outputs of the verifier is used to deduce the secret mapping functions and the embedded logo within an uncertainty of two possibilities. The deduced mapping functions are then used to modify the content of an authenticated image without detection or to authenticate an arbitrary image of the same size. Note that the logo is not used in the forgery so sophisticated protection of the logo cannot thwart the atta . Our attack is very efficient. Only 255 trials are needed to attack an 8-bit grayscale image and 765 trails for a 24-bit color image. The proposed attack can also be applied to attack pixel-wise variations of the Y-M scheme proposed to fix the previously reported vulnerabilities.